Mechanistic insights into nicotine withdrawal - Paolini, Michael (2011)
Smoking is responsible for over 400,000 premature deaths in the United States every year, making it the leading cause of preventable death. In addition, smoking-related illness leads to billions of dollars in healthcare expenditures and lost productivity annually. The public is increasingly aware that successfully abstaining from smoking at any age can add years to one’s life and reduce many of the harmful effects of smoking. Although the majority of smokers desire to quit, only a small fraction of attempts to quit are actually successful. The symptoms associated with nicotine withdrawal are a primary deterrent to cessation and they need to be quelled to avoid early relapse. This review will focus on the neuroadaptations caused by chronic nicotine exposure and discuss how those changes lead to a withdrawal syndrome upon smoking cessation. Besides examining how nicotine usurps the endogenous reward system, we will discuss how the habenula is part of a circuit that plays a critical role in the aversive effects of high nicotine doses and nicotine withdrawal. We will also provide an updated summary of the role of various nicotinic receptor subtypes in the mechanisms of withdrawal. This growing knowledge provides mechanistic insights into current and future smoking cessation therapies.